Taxonomia de Bloom como ferramenta para avaliação da aprendizagem em um curso de medicina que utiliza métodos ativos de aprendizagem - Machado, Durvalino Vieira (2018)
Introduction: This research analyzed the use of the Bloom Taxonomy by medical students in the Tutorial Module Course Unit during the progression of these students from the first to the eighth period. Objective: To evaluate the verbs used by the students in their learning objectives construction. Methodology: Cross-sectional, descriptive, retrospective and quantitative approach study. The non-probabilistic convenience sample was composed of 511 concept maps referring to eight academic semesters, from 2013-2 to 2017-1, where the learning objectives were recorded. The data was recorded on the Excel web platform (Portal Action) of the Google Forms Software. There were included 3.480 items classified as truly learning objectives, submitted to descriptive statistical analysis with average and standard deviation; Pearson's inference analysis at 5% for normal distribution data; Kolmogorov-Smirnov test with 5% normality level significance for non-normal data, in addition to Kruskal Wallis analysis for comparison of learning categories averages. Statistical analysis and graphs were compiled in Excel Software, IBM SPSS statistics 222 version, 2013 and GraphPad Prism, 5 version, 2007. Results: The data point to homogeneous sample with average dispersion, being the variation coefficient of the maps performed of 17.58% and those found of 21.29%; the data related to the maps performed and those found have a non-parametric distribution (p-value = 0.046 and p-value = 0.013, respectively). The 'Knowledge' category was composed by 912 (26.20%) verbs of the total; the 'Understanding' category was composed by the largest number of verbs 2,371 (68.13%); the 'Application' category was composed by 17 (0.48%); the 'Analysis' category by 167 (4.79%); the 'Synthesis' category by 7 (0.20%) and the 'Assessment' category by 6 (0,17%) verbs. The semester average of verbs used by the students was 435 (± 55.94). In the 'Knowledge' and 'Understanding' categories the students used a large amount of the verbs known and understood, which are not on the list presented by Bloom. Conclusion: There was a progressive increase in the students’ use of taxonomy verbs from the less complex to the more complex categories, with higher evidence in the seventh and eighth periods, as the course progressed. It was concluded the need of teacher and student training to use the Bloom Taxonomy as an optimizer of the method’s use. It was inferred that the use of verbs of the 'Knowledge' and 'Understanding' categories stems from the great amount of curricular contents unpublished throughout the curricular matrix, although the spiral design and transversality of the investigated Curricular Unit